Sosialisasi Pemahaman Konsep Bauran Pemaran 4P dan Pemasaran Online pada Masyarakat yang Berdampak Banjir di Aceh Tamiang - Hadian, Arief; Batubara , Ismed; Saragih, Alkausar; Hasibuan, Hadi Halomoan; Natasya, Natasya (Indonesia Berdampak: Jurnal Pengabdian kepada Masyarakat, 2026)
This community service activity aimed to enhance the understanding and capabilities of small business actors in applying the Marketing Mix 4P (product, price, place, and promotion) among flood-affected communities in Aceh Tamiang Regency. The method used was socialization through interactive lectures, discussions, and practical guidance on adaptive marketing strategies in post-disaster conditions. The results showed a significant improvement in participants’ knowledge and skills. Participants became more aware of the importance of adjusting products to current market needs, particularly by offering practical and essential goods. In terms of pricing, they understood the need to set flexible and affordable prices aligned with decreased purchasing power. Regarding place (distribution), participants gained insights into utilizing both direct and digital channels, including social media and messaging platforms, to expand market reach. In the promotion aspect, they demonstrated increased interest in applying simple yet effective promotional strategies, such as using digital media, customer testimonials, and community networks. Furthermore, participants were able to integrate the four elements of the marketing mix more effectively in managing their businesses. These findings are consistent with previous studies highlighting that the implementation of the 4P marketing mix, especially when supported by digital tools, can improve competitiveness and business sustainability. Therefore, this activity contributes positively to economic recovery and business resilience in post-disaster communities.